2022
DOI: 10.3389/fnhum.2022.829745
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Measurements of Electric Fields During Cranial Electrical Stimulation in the Human Brain

Abstract: Cranial electrical stimulation (CES) has been applied at various current levels in both adults and children with neurological conditions with seemingly promising but somewhat inconsistent results. Stimulation-induced spatial electric fields (EFs) within a specific brain region are likely a significant contributing factor for the biological effects. Although several simulation models have been used to predict EF distributions in the brain, these models actually have not been validated by in vivo CES-induced EF … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 43 publications
1
7
0
Order By: Relevance
“…As displayed in Figure 4 B, we also found a moderate correlation between the measured and simulated values in the EF distributions ( r = 0.58, p < 0.001; s = 0.44). In line with several previous studies [ 16 , 27 ], we found a lower correlation between measured and simulated EF, in contrast to voltage values.…”
Section: Measured and Simulated Electric Field Of Tessupporting
confidence: 92%
See 1 more Smart Citation
“…As displayed in Figure 4 B, we also found a moderate correlation between the measured and simulated values in the EF distributions ( r = 0.58, p < 0.001; s = 0.44). In line with several previous studies [ 16 , 27 ], we found a lower correlation between measured and simulated EF, in contrast to voltage values.…”
Section: Measured and Simulated Electric Field Of Tessupporting
confidence: 92%
“…In this case report, our results show that the EF modeling can effectively predict EF distribution during tES in the lesioned brain under various electrical stimulation montages. The simulation model is also validated via in vivo measurement in previous studies of the non-lesioned brain [ 16 , 27 ]; they found a higher correlation between the simulated and predicted EF (Huang et al: r = 0.89; Wang et al: r = 0.73). These results indicated the influence of brain lesions on model performance.…”
Section: Discussionmentioning
confidence: 81%
“…First, the calculated e-field in this study is based on the individual anatomical features, meaning that it is only a proxy for the real e-field and stimulation. A kind of e-field validation can be obtained through in-vivo invasive electrophysiological recordings ( Opitz et al, 2018 , Wang et al, 2022 ). Second, in the present study, e-field modeling was based on the T1-weighted anatomical scans.…”
Section: Discussionmentioning
confidence: 99%
“…The induced field distribution by transcranial stimulation might depend on multiple stimulation parameters such as time, intensity and duration of stimulation (Lerner et al, 2021;Sandrini et al, 2011;Westwood and Romani, 2017;Yeh and Rose, 2019), which makes the location and size of the stimulated cortical areas difficult to define accurately (Karabanov et al, 2019;Laakso et al, 2018;Weise et al, 2020). TES has a low spatial resolution, rendering selective stimulation of the AG without concomitant stimulation of nearby areas extremely difficult, as evidenced by simulations and in vivo measurements (Saturnino et al, 2019;Wang et al, 2022). The spatial resolution of TMS (Deng et al, 2013) is generally higher than that of TES, but TMS over the AG can also often induce relatively high stimulation intensities in other nearby areas (Kuhnke et al, 2020a), as mentioned above.…”
Section: Low Spatial Resolution Of Tms/tesmentioning
confidence: 99%